Complete Genome Sequence of Escherichia albertii Strain 1551-2, a Potential Extracellular and Intracellular Pathogen - Romao, Fabiano Teodoro; Hernandes, Rodrigo Tavanelli [UNESP]; Ooka, Tadasuke; Hayashi, Tetsuya; Sperandio, Vanessa; Tardelli Gomes, Tania Aparecida (Amer Soc Microbiology, 2018)
Escherichia albertii has recently been recognized as an emerging human and bird enteric pathogen. Here, we report the complete chromosome sequence of a clinical isolate of E. albertii strain 1551-2, which may provide information about the pathogenic potential of this new species and the mechanisms of evolution of Escherichia species.